Food Poisoning and Its Prevention on the Example of Listeria Monocytogenes - Ekaterina Savelyeva (Journal of Global Pharma Technology, 2020)
Listeriosis is one of the most serious and severe foodborne diseases characterized by a high mortality rate of 20% to 44%. The purpose of the research is to study the age-related features of the clinical symptoms of listeriosis in adults, as well as the influence of comorbid conditions on its course. The study included 73 patients with listeriosis (43 (58.9%) men and 30 (41.1%) women; average age (48.83 ± 6.29) years). They were divided into 2 groups: group 1 (n = 29) - patients aged 18-49 years, group 2 (n = 44) - patients aged over 50 years. Septicemia is most common clinical syndrome in patients with listeriosis, presented in 46 (63%) patients. It’s followed by damages of the central nervous system, namely meningitis and meningoencephalitis in 26 (35.6%) patients; gastroenteritis in 10 (13.7%) patients; and skin lesions in 3 (4.1%) patients. Septicemia was a typical clinical syndrome for patients over 50 years old - in 33 (75%) patients compering to 13 (44.8%) in the younger age group (OR = 3.69, 95% CI [1.36-10.04]). The damages of the central nervous system, namely meningitis and meningoencephalitis were typical for younger age group - 16 (55.2%) patients while 10 (22.7%) cases among the older age group (OR = 4.18, 95% CI [1, 51-11.56]). The mortality rate was 27.4% (of which 80% of deaths occurred in the older age group). Listeriosis is characterized by a severe course and a high mortality rate from septicemia and CNS damages. It is the cause of concomitant pathology development in immunocompromised individuals. Keywords: Adult listeriosis, Age-related features of listeriosis, mortality in listeriosis, Comorbid conditions and listeriosis, Prevention of listeriosis.